DESIGNING AND DEVELOPING A PERSUASIVE MOBILE APPLICATION FOR ORAL HEALTH PROMOTION: A METHODOLOGY - Siti Mahfuzah Sarif; Siti Izani Idris, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Maintaining excellent oral hygiene could be very challenging, but it can be aided by employing appropriate motivational approaches. Flossing is one of the critical oral hygiene habits. This paper discusses the design and development of mobile application that could motivate user to learn, perform, and maintain optimal oral hygiene. Applying persuasive design in the development of oral health-related mobile applications could promote this good habit. Thus, the primary focus of this paper is to elaborate on the methodology of finding out a set of design principles under persuasive design for developing a mobile application that could engage user in maintaining good oral hygiene in general. The mobile application also aims to motivate user to take care of their oral hygiene through flossing activities. This paper discusses the design solution through a human-centred process; Design Thinking method. There are five phases in Design Thinking; however, this paper focuses on elaborating the first four phases: Empathy, Define, Ideate, and Prototype. 44 respondents were involved in the process of acquiring the requirements for design and development of a persuasive mobile application for promoting oral health. Finally, a high-fidelity prototype of the mobile application was produced and named as the FlossDance App.